Forms as Simple and Individual Grounds of Things' Natures. (21st May 2018) - Koons, Robert C.
To understand Aristotle's conception of form, we have to see clearly the relationship between his account and Plato's Theory of Forms. I offer a novel interpretation of Aristotle's Moderate Realism, in which forms are simple particulars that ground the character and mutual similarity of the entities they inform. Such an account has advantages in three areas: explaining (1) the similarity of particulars, (2) the synchronic unity of composite particulars, and (3) the diachronic unity or persistence of intrinsically changing particulars.